Business Development Strategy with SWOT Analysis Method at PT Jaho Mulya Sunjaya - Amelia Mutiara Zahrani; Mochamad Heru Riza Chakim; Mulyati Mulyati (International Journal Labs, 2025)
Digital marketing has become one of the most effective tools in increasing brand awareness, especially in the academic environment. This study aims to evaluate the effectiveness of digital marketing strategies implemented at Raharja University in increasing brand awareness among students and prospective students. The methods used in this study are surveys and quantitative data analysis, with the population of active students and prospective students who register. The results show that the use of social media and digital content significantly contributes to increasing brand awareness. This research provides important insights for the university in formulating a more effective and efficient marketing strategy.